Interface modification of Cr/Ti multilayers with C barrier layer for enhanced reflectivity in the water window regime. (13th November 2020) - Sarkar, P.; Biswas, A.; Abharana, N.; Rai, S.; Modi, M. H.; Bhattacharyya, D.
Abstract : By modifications of the interface of Cr/Ti multilayers using an ultra‐thin carbon buffer layer at each interface, remarkable improvement of the soft X‐ray reflectivity of the multilayers in the water window region has been achieved. Abstract : The influence of a carbon barrier layer to improve the reflectivity of Cr/Ti multilayers, intended to be used in the water window wavelength regime, is investigated. Specular grazing‐incidence X‐ray reflectivity results of Cr/Ti multilayers with 10 bilayers show that interface widths are reduced to ∼0.24 nm upon introduction of a ∼0.3 nm C barrier layer at each Cr‐on‐Ti interface. As the number of bilayers increases to 75, a multilayer with C barrier layers maintains almost the same interface widths with no cumulative increase in interface imperfections. Using such interface‐engineered Cr/C/Ti multilayers, a remarkably high soft X‐ray reflectivity of ∼31.6% is achieved at a wavelength of 2.77 nm and at a grazing angle of incidence of 16.2°, which is the highest reflectivity reported so far in the literature in this wavelength regime. Further investigation of the multilayers by diffused grazing‐incidence X‐ray reflectivity and grazing‐incidence extended X‐ray absorption fine‐structure measurements using synchrotron radiation suggests that the improvement in interface microstructure can be attributed to significant suppression of inter‐diffusion at Cr/Ti interfaces by the introduction of C barrier layers and also due to the smoothing effect of the C layer promoting two‐dimensional growth of the multilayer.